Health Poems Intervention for Awareness of Polio and Routine Immunization Among Rural Children of Pakistan - Ram(Jewat Sunder), Jewat; Jewat, Satti; Shaikh, Sirajul Haque; Ahmed, Farah; Danish, Hassan (Infectious Diseases Journal of Pakistan, 2022)
Objective: To evaluate the impact of health poems intervention for awareness of polio and routine immunization among rural children at Sethar Pir District Sanghar. Materials and Methods: This was a quasi-experimental trial conducted at Sethar Pir District Sanghar from August 2017 to December 2018. Two fifty students of primary schools of age 9-15 years of either gender were included in the study. The students were approached during the free period and the questionnaire (study tool) was filled by them in 15-20 minutes. After that the educational intervention i.e. a health poem regarding the importance of routine immunization and polio eradication with schedule of the vaccination status written was given in syllabus. The three session of health poem were given after every week for 21 days to all the students and the printed materials were pasted on the books of the students for further memorization. After completion of three sessions the post intervention data from the same students through the use of study instrument (which was administered before the intervention) was collected to see impact. SPSS version 23 was used to analyze the before and after intervention data. Results: Total of 250 primary students were included in the study. The mean age of students was reported as 13.45±1.21 years. Two hundred and five students were males (82%) and 45 students were females (18%). The frequency of adequate awareness showed statistically significant increase after the health poem intervention as compared to before (p<0.05). The health poem intervention was an ideal and innovative method to increase the awareness &has shown successful results among primary school going children of District Sanghar. Keywords: Health poem intervention, Impact of educational intervention, Rural area, Primary school, Awareness of polio, Routine immunization.